THE INFLUENCE OF TAX PLANNING, TUNNELING INCENTIVE, INTANGIBLE ASSET, AND PROFITABILITY ON TRANSFER PRICING DECISIONS IN MULTINATIONAL FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Fazwa, Monika; Islahuddin, Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study is aimed to examine the influence of tax planning, tunneling incentive, intangible asset, and profitability on transfer pricing decisions. This study tested the hypotheses in food and beverage companies listed in Indonesia Stock Exchange (IDX) from 2016 to 2020. By using the purposive sampling technique, 12 out of 33 companies in the food and beverage sector were taken as a sample with a total of 60 data observations. The data was then analyzed through multiple linear regression analysis. The results of this study revealed that all independent variables simultaneously affect the dependent variable. Partially, the finding of tax planning and tunneling incentive has a positive effect but not significant on transfer pricing. However, intangible asset and profitability has a positive and significant effect on transfer pricing, means that intangible asset and profitability is engaged on transfer pricing decisions of food and beverage companies listed in Indonesia Stock Exchange (IDX).